MeerKAT's discovery of a radio relic in the bimodal merging cluster A2384. Issue 1 (21st September 2020) - Parekh, V; Thorat, K; Kale, R; Hugo, B; Oozeer, N; Makhathini, S; Kleiner, D; White, S V; Józsa, G I G; Smirnov, O; van der Heyden, K; Perkins, S; et al.
ABSTRACT: We present the discovery of a single radio relic located at the edge of the galaxy cluster A2384, using the MeerKAT radio telescope. A2384 is a nearby ( z = 0.092), low-mass, complex bimodal, merging galaxy cluster that displays a dense X-ray filament (∼700 kpc in length) between A2384(N; northern cluster) and A2384(S; southern cluster). The origin of the radio relic is puzzling. Using the MeerKAT observation of A2384, we estimate that the physical size of the radio relic is 824 × 264 kpc 2 and that it is a steep spectrum source. The radio power of the relic is P_1.4GHz (3.87 ± 0.40) × 10 23 W Hz −1 . This radio relic could be the result of shock wave propagation during the passage of the low-mass A2384(S) cluster through the massive A2384(N) cluster, creating a trail appearing as a hot X-ray filament. In the previous GMRT 325 MHz observation, we detected a peculiar FR I radio galaxy interacting with the hot X-ray filament of A2384, but the extended radio relic was not detected; it was confused with the southern lobe of the FR I galaxy. This newly detected radio relic is elongated and perpendicular to the merger axis, as seen in other relic clusters. In addition to the relic, we notice a candidate radio ridge in the hot X-ray filament. The physical size of the radio ridge source is ∼182 × 129 kpc 2 . Detection of the diffuse radio sources in the X-ray filament is a rare phenomenon, and could be a new class of radio source found between the two merging clusters of A2384(N) and A2384(S).